Enhancing teacher competence through collaborative worksheet development: an empirical investigation - Meilinda Meilinda; Ratu Ilma Indra Putri; Zulkardi Zulkardi; Rita Inderawati; Try Desnita (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study examined the efficacy of collaborative teaching using a projectbased learning (PjBL) worksheet on plastic waste and climate change. The research design followed a type-II development approach, with two distinct phases: exploration and development, and collaborative teaching. The study involved five science teachers, two lecturers, and 45 seventh-grade students in three limited field trials. The study found that collaborative teaching through worksheet development could increase science teachers’ professionalism, particularly in the collegial phase. Furthermore, the study developed a valid PjBL-based worksheet on plastic waste and climate change, aligning with the 2013 curriculum for science instruction in junior high school, involving three core competencies. The research design employed a lesson study framework, which allowed for a thorough exploration of the research topic, leading to the development of effective instructional material. The findings of this study have significant implications for science education in junior high school, particularly in promoting active learning and fostering a deeper understanding of complex environmental issues. Overall, the study highlights the importance of collaborative teaching and the potential of PjBL-based worksheets in enhancing teacher competence and developing relevant instructional materials that align with the curriculum.